2011
DOI: 10.1111/j.1439-0264.2011.01096.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Oestrogen Receptors in Foetal Lung Tissue of Mice

Abstract: Oestrogens are responsible for the sexual dimorphism in adult mice lung tissue, and this difference is most notable at sexual maturity. Oestrogen receptor-alpha (ERα) and the oestrogen receptor-beta (ERβ) are the two receptors that mediate oestrogen action, but adult mice lung tissue only expresses ERβ, and it is probably through this receptor that oestrogens exert their action. The goal of our study was to detect the expression of ERα and ERβ in mouse foetal lung tissues and identify possible gender differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…In recent years, studies investigating the expression and function of ERβ have proven helpful for elucidating the mechanism by which ERβ functions . In our study, we investigated the expression of ERβ (especially ERβ1 and ERβ2) in LADE of mice, consistent with the previous studies . FQ‐PCR showed that the mRNA expression of ERβ and ERβ2 in the E2 group was significantly higher than that in the E2+Ful group and control group.…”
Section: Discussionsupporting
confidence: 80%
“…In recent years, studies investigating the expression and function of ERβ have proven helpful for elucidating the mechanism by which ERβ functions . In our study, we investigated the expression of ERβ (especially ERβ1 and ERβ2) in LADE of mice, consistent with the previous studies . FQ‐PCR showed that the mRNA expression of ERβ and ERβ2 in the E2 group was significantly higher than that in the E2+Ful group and control group.…”
Section: Discussionsupporting
confidence: 80%
“…Evaluation of the TPS profile suggests that the Esr2 decreases briefly after birth, followed by an increase from around day 5 until day 20 whereas non-optimized profile suggests a relatively flat profile. While fetal mouse lungs express both Esr2 alpha and beta, adult mouse lungs express only Esr2 beta consistent with the TPSresults ( Carvalho and Goncalves, 2012 ). Igfbp3 : Insulin-like growth factor binding protein 3 ( Igfbp3 ) belongs to the Igfbp family and has a Igfbp domain and a thyroglobulin type-I domain ( http://www.ncbi.nlm.nih.gov/gene/3486 ).…”
Section: Selecting the Set Of 126 Genessupporting
confidence: 62%
“…Evaluation of the TPS profile suggests that the Esr2 decreases briefly after birth, followed by an increase from around day 5 until day 20 whereas non-optimized profile suggests a relatively flat profile. While fetal mouse lungs express both Esr2 alpha and beta, adult mouse lungs express only Esr2 beta consistent with the TPSresults ( Carvalho and Goncalves, 2012 ).…”
supporting
confidence: 62%
“…This is important because estrogen can cause effects on the immune system by binding to estrogen receptors (ER) expressed by immune cells, such as B cells, T cells, and macrophages [138]. Variations in the expression of ER in the bronchial and alveolar epithelium suggest a role in estrogen signaling, which can contribute to the gender dimorphism seen in males and females [130,131,139,140]. In addition, estrogen has the ability to indirectly stimulate airway and parenchymal responses by acting on airway and alveolar epithelial cells, which are structural cells [141].…”
Section: Effect Of Sex Hormones In Immune Responses and Lung Developmentmentioning
confidence: 99%